Pulmonary hydatid disease - le Roux, B. T. (1972)
Radiographic evidence is presented in confirmation of the contention that uncomplicated isolated pulmonary hydatid cysts are seldom completely circular and can be confidently recognized as hydatid cysts radiographically and fluoroscopically.